Information Sources Used by Visitors Looking for Different Benefits: The Case of Portorož - Nemec Rudež, Helena; Sedmak, Gorazd; Bojnec, Štefan (Naše gospodarstvo/Our economy, 2012)
This paper examines the information sources of visitors to Portorož for four identified distinct clusters of visitors. The study focused on using a single one source of infor- mation about Portorož regardless of the cluster to which the visitors belonged. The Internet and brochures were identified as the most important sources of information in general. The cluster defined as “well-being visitors” demonstrated a significantly different structure of information sources, relying predominantly on brochures and the Internet. Unlike first-time visitors, regular visitors indicated a relatively low per- centage of Internet and brochure use.